PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN KESEMPATAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING - Tri Anitawati, 12.52.02.0208 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The value of the company is very important because of the high value of the company which will be followed by higher shareholder wealth. The higher the stock price higher the value of the company, to achieve the companys value investors generally handed management to professionals. This study aimed to determine the effect of ROA, ROE, IOS on the value of the companys dividend policy as moderating variables. The population in this study are all companies listed on the Stock Exchange. Method of sampling is done with purposive sampling method, and based on predetermined criteria, the number of samples is a sample of 111 manufacturing firms during the period 2010-2012. The research data is secondary data obtained from ICMD 2010-2012. Research hypothesis testing used multiple analysis techniques and moderated regression analysis, with tools SPSS (Statistical Product and Service Solutions). The results showed that: 1) ROA positive and significant effect on the value of the company, 2) ROE significant negative effect on firm value, 3) IOS significant positive effect on firm value, 4) Parliament a significant negative effect on the value of the company 5) dividend policy is able to significantly moderate the influence of ROA on the value of the company, 6) dividend policy is able to significantly moderate effect on firm value ROE, 7) dividend policy is able to significantly moderate the influence of IOS on firm value. Keywords: retun on assets, return on equity, investment opportunity set, the dividend payout ratio and the value of the company